A systematic approach towards the prevention of the laboratory errors and the optimization of the preanalytical phase management - Oliveira, Gabriel de Souza Lima (2017)
Orientadores : Gian Cesare Guidi (Università degli Studi di Verona), Geraldo Picheth (Universidade Federal do Paraná)